Response from Varani et al. to “Comment on ‘the IS6 family, a clinically important group of insertion sequences including IS26’ by Ruth M. Hall” - Varani, Alessandro [UNESP]; He, Susu; Siguier, Patricia; Ross, Karen; Chandler, Michael (Springer Nature, 2022)
The IS6 family of insertion sequences is a large but coherent group which was originally named to avoid confusion between a number of identical or nearly identical IS that were identified at about the same time and given different names (IS15D, IS26, IS46, IS140, IS160, IS176). The underlying common mechanistic feature of all IS6 family members which have been investigated is that they appear to transpose by replicative transposition and form pseudo compound transposons with the flanking IS in direct repeat and in which associated genes are simply transferred to the target replicon and lost from the donor. In the accompanying letter Hall raises a number of very serious and wide-ranging criticisms of our recent review article concerning the IS6 family of insertion sequences. She clearly feels that we have undervalued her work and that we question or ignore certain of her in vivo results. This impression is almost certainly the result of the standard of proof we generally apply to mechanistic aspects of transposition where we think it important to identify transposition intermediates including the types of synaptic, strand cleavage and strand transfer complexes involved.